2018
DOI: 10.1111/maps.13211
|View full text |Cite
|
Sign up to set email alerts
|

High‐mass resolution molecular imaging of organic compounds on the surface of Murchison meteorite

Abstract: High‐resolution mass spectrometry (HRMS) imaging by desorption electrospray ionization (DESI) coupled with Orbitrap MS using methanol (MeOH) spray was performed on a fragment of the Murchison (CM2) meteorite in this study. Homologues of CnH2n–1N2+ (n = 7–9) and CnH2nNO+ (n = 9–14) were detected on the sample surface by the imaging. A high‐performance liquid chromatography (HPLC)/HRMS analysis of MeOH extracts from the sample surface after DESI/HRMS imaging indicated that the CnH2n–1N2+ homologues corresponds t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 38 publications
3
18
2
Order By: Relevance
“…This is in contrast with a previous DESI/HRMS study of the Murray meteorite, which found that the alkylimidazole and alkylpyridine compounds occurred in different locations-that is, these two homologous CHN series were not co-located [17]. Furthermore, a previous DESI/HRMS study of the Murchison meteorite found only alkylimidazole compounds, and no alkylpyridine compounds were detected [18].…”
Section: Desi/hrms Analysiscontrasting
confidence: 97%
See 4 more Smart Citations
“…This is in contrast with a previous DESI/HRMS study of the Murray meteorite, which found that the alkylimidazole and alkylpyridine compounds occurred in different locations-that is, these two homologous CHN series were not co-located [17]. Furthermore, a previous DESI/HRMS study of the Murchison meteorite found only alkylimidazole compounds, and no alkylpyridine compounds were detected [18].…”
Section: Desi/hrms Analysiscontrasting
confidence: 97%
“…Using a spray of electrically charged solvent such as methanol, soluble organic compounds are desorbed and ionized from the sample for introduction to a mass spectrometer, with a typical surface spatial resolution of 50-100 µm. Molecular imaging of the surface of the Murray and Murchison meteorites were performed by DESI/HRMS, and various alkylated CHN homologous compounds were identified [17,18]. These CHN compounds were distributed heterogeneously in the matrices of both meteorites.…”
Section: Organic Compound Imaging By In Situ Analysismentioning
confidence: 99%
See 3 more Smart Citations